Efektivitas Komunikasi Pemasaran Personal Selling pada Agrowisata Kampung 99 Pepohonan - Januariska Bayu Dwinanda; Ninuk Purnaningsih (Jurnal Komunikasi Pembangunan, 2018)
Marketing communication by community based agrotourism marketer are needed so that many people are interested to visit and utilize the products or services offered. Personal selling is one form of marketing communication conducted by Kampung 99 Pepohonan Agrotourism. This paper aims to analyze the effectiveness of personal selling as marketing communication at Kampung 99 Pepohonan Agrotourism which the one of community based agrotourism and analyze the factors that influence the effectiveness of personal selling as marketing communication. This research uses census method by using quantitative data in the form of questionnaires supported by qualitative data in the form of interview with informant. The results showed that the effectiveness of personal selling as marketing communications on cognitive aspect influenced by marketing communication skills variable and the completeness of message content variable, while the effectiveness of personal selling as marketing communication on affective and conative aspects influenced by messages delivery strategy.